Analysis Of Uric Acid Levels In Pre-Elderly Patients In Terms Of Coffee Drinking Behavior In The Work Area Of The Cikeusal Health Center, Serang Regency In 2022 - Heni Nurfajar; Omega DR Tahun (International Journal of Health and Pharmaceutical (IJHP), 2023)
The World Health Organization (WHO) states that hyperuricemia sufferers are increasing every year in the world. The Cikeusal Health Center in Serang Regency shows that cases of hyperuricemia are quite high, namely as many as 189 in 2020, increasing in 2021, namely 340, even in 2022 in the January-September period there were 208 cases. One of the pharmacological treatments in the treatment of hyperuricemia is coffee because it contains polyphenolic compounds. Purpose of Writing was to knowing the analysis of uric acid levels in pre-elderly patients in terms of coffee drinking behavior in the working area of the Cikeusal Health Center, Serang Regency, in 2022. Research Methods on this research is a quantitative analytic study with a cross sectional design. The sample in this study were pre-elderly patients who visited the Cikeusal Health Center in Serang Regency in August-October 2022 with a total of 81 respondents using a purposive sampling technique. The research instrument used questionnaires and observation sheets. The data is primary data analyzed using the one way ANOVA test which previously had been carried out the normality test with normal data distribution results. The results of univariate analysis revealed that the average uric acid level was 4.786, coffee drinking behavior was low, medium and high respectively 33.3% with an average of 21.07. The results of the bivariate analysis revealed that there was an effect of coffee drinking behavior on uric acid levels with a p value = 0.021. Coffee drinking behavior affects uric acid levels in pre-elderly patients. It is hoped that the community can carry out routine checks and maintain food intake, one of which is drinking coffee regularly between 1-2 times a day.